The measurement of ancestral roots with genealogical data. Issue 4 (2nd October 2017) - Tremblay, Marc
ABSTRACT: This study presents a new method to measure the depth of ancestral roots in a population. This method sheds light on the migratory movements that led to present-day population distribution across space. The method was applied to a dataset of 5, 100 ascending genealogies from 17 regions of the province of Quebec (Canada). Dates of marriage of the earliest ancestors married in the same region as their descendants were used to measure the age of individual ancestral roots. The average regional ages vary between 16 and 157 years, while some individual roots reach as far back as 300 years in the same region. The proposed method can be useful for assessing how deeply rooted a contemporary population is at a local, regional, or other geographical level.